Impact of initial biopsy type on the time to final diagnostic biopsy in patients with follicular lymphoma and suspected histologic transformation. Issue 12 (15th October 2021) - Mou, Eric; Falchi, Lorenzo; Sundaram, Vandana; Abramson, Jeremy S.; Balassanian, Ronald; Beygi, Sara; Fitzpatrick, Megan J.; Frank, Annabel Kate; Gupta, Srishti; Lin, Oscar; Reed, Joshua R.; Long, Steven R.; et al.
Abstract: Diagnosis of histologic transformation (HT) of follicular lymphoma (FL) requires tissue biopsy. While surgical biopsy represents the gold standard, less invasive procedures such as fine-needle aspiration biopsy (FNAB) and core needle biopsy (CNB) are frequently performed. In this retrospective multi-institutional study including 269 patients with FL and suspected HT, the median time from initial clinical suspicion to final diagnostic biopsy was similar whether the workup began with FNAB, CNB, or surgical biopsy (4, 9, and 6 days, respectively; p =.27), despite more subsequent biopsies performed following initial FNAB. Periprocedural complications were uniformly minimal. Biopsy-proven HT was more common in the initial surgery group and in workups including positron emission tomography/computed tomography (PET/CT). Our findings, derived from US academic centers with specialized procedural and pathology expertise, suggest that FNAB, CNB, and surgical biopsy are all viable initial diagnostic procedures that can inform clinical decision-making in select FL patients with suspected HT.